Simultaneous Detection of 13 Key Bacterial Respiratory Pathogens by Combination of Multiplex PCR and Capillary Electrophoresis - JIANG, Lu Xi; REN, Hong Yu; ZHOU, Hai Jian; ZHAO, Si Hong; HOU, Bo Yan; YAN, Jian Ping; QIN, Tian; CHEN, Yu (Biomedical and environmental sciences, 2017)
Objective Lower respiratory tract infections continue to pose a significant threat to human health. It is important to accurately and rapidly detect respiratory bacteria. To compensate for the limits of current respiratory bacteria detection methods, we developed a combination of multiplex polymerase chain reaction （PCR） and capillary electrophoresis （MPCE） assay to detect thirteen bacterial pathogens responsible for lower respiratory tract infections, including Streptococcus pneumoniae, Haemophilus influenzae, Moraxella catorrholis, Pseudomonas aeruginosa, Klebsiella pneumoniae, Escherichia coli, Staphylococcus aureus, Mycoplasma pneumoniae, Legionella spp., Bordetella pertussis, Mycobacterium tuberculosis complex, Corynebactefium diphthefiae, and Streptococcus pyogenes. Methods Three multiplex PCR reactions were built, and the products were analyzed by capillary electrophoresis using the high-throughput DNA analyzer. The specificity of the MPCE assay was examined and the detection limit was evaluated using DNA samples from each bacterial strain and the simulative samples of each strain. This assay was further evaluated using 152 clinical specimens and compared with real-time PCR reactions. For this assay, three nested-multiplex-PCRs were used to detect these clinical specimens. Results The detection limits of the MPCE assay for the 13 pathogens were very low and ranged from 10-7 to 10-2 ng/μL. Furthermore, analysis of the 252 clinical specimens yielded a specificity ranging from 96.5%-100.0%, and a sensitivity of 100.0% for the 13 pathogens. Conclusion This study revealed that the MPCE with high specificity and sensitivity. This assay survey of respiratory pathogens. assay is a rapid, reliable, and high-throughput method has great potential in the molecular epidemiological.